Comparison of Secretome Dental Pulp Stem Cell And Mebo Ointment on The Amount of Fibroblast and Collagen In Superficial Dermal Burns - Loviana Hasibuan, Soya; Fibrini, Dewi; Tjipta, Arya; Ruspita, Intan; Yolanda, Eva (Syntax Corporation Indonesia, 2024)
Secretome Dental Pulp Stem Cells have been proposed as a new alternative for wound burn. The aim of this study is to compare Secretome Dental Pulp Stem Cells and MEBO ointment against several fibroblasts and collagen in the healing process of superficial dermal burns. This study used a post-test only controlled group design by using 15 rats that were given superficial dermal burned wounds. Rats were divided into a negative control group of NaCl 0.9% (K1), a treatment group of MEBO (K2), and a treatment group of DPSCs-secretome (K3). Histopathology was done on the 5th, 14th, and 21st days post-induction wound burn. Network-prepared histopathology by colouring Messon Trichomes. Then, it was observed under a microscope with 200x magnification. Scoring in a way semi-qualitative for assessing fibroblasts and collagen. The total score of fibroblasts in the MEBO group was higher than the DPSCs-secretome group on day 5th. In comparison, the score for increasing the amount of collagen in the DPSCs-secretome group on days 5th and 14th was higher than the MEBO group. DPSCs-secretome has better effectiveness in increasing the amount of collagen but not better in increasing fibroblasts compared to MEBO.